Techniques of Anti-sway and Input Tracking Control of a Gantry Crane System - Mohd Ashraf, Ahmad; Ahmad Nor Kasruddin, Nasir; Haszuraidah, Ishak (2009)
This paper presents investigations into the development of control schemes for anti-swaying and input tracking control of a gantry crane system. A nonlinear overhead gantry crane system is considered and the dynamic model of the system is derived using the Euler-Lagrange formulation. To study the effectiveness ofthecontrollers, initially a collocated PD control is developed for cart position control of gantry crane. This is then extended to incorporate a non-collocated PID and an input shaper control schemes for anti-swaying control of the system. The positive input shapers with the derivative effects are designed based on the properties of the system. Simulation results of the response of the gantry crane with the controllers are presented in time and frequency domains. The performances of the control schemes are examined in terms of level of input tracking capability, swing angle reduction and time response specifications in comparison to the PD control. Finally, a comparative assessment of the control techniques is presented and discussed.